Differential effects of mindfulness treatment and mobile neurofeedback on event-related potentials in early posterior negativity in cancer patients: a clinical-experimental parallel group design - Fink, Madeleine; Schmidt, Kira; Kowalski, Axel; Pasche, Saskia; Albrot, Calvin; Krawutschke, Marvin; Schweig, Theresa; Tewes, Mitra; Skoda, Eva-Maria; Teufel, Martin; Müller, Bernhard W. (Frontiers in Psychology, 2024)
Introduction Cancer frequently leads to psychological challenges, among them emotion regulation problems. These can be alleviated with the help of mindfulness therapies or neurofeedback (NF) interventions. Possible intervention effects on emotion procession can be detected in clinical EEG studies by exploring event-related potentials, e.g., early posterior negativity (EPN), which recently has been established to investigate emotional processing and represents very early attention to affective stimuli. Therefore, this clinical-experimental study investigated the efficacy of mindfulness and NF (10 sessions each) on the EPN in oncology patients. Method The study enrolled 42 cancer patients (age: 31–73 years; gender: 28 female, 14 male). The study design was an RCT with a parallel group [NF (n = 21) versus mindfulness (n = 21)] waitlist paradigm. EEG recordings in an oddball task with neutral, rare positive and negative valence and high and low arousal stimuli were performed at three measurement time points (T0 = before waitlist, T1 = before intervention, T2 = after intervention). Following preprocessing, data from electrodes O1, Oz and O2 were analyzed for EPN amplitudes. Results Response time did not differ across groups and conditions. Comparing EPN at T1 and T2, there was a significant interaction of time, valence, and intervention (p = 0.042). Descriptive statistics showed increased EPN for negative stimuli after the NF intervention (T1 to T2), while EPN for positive stimuli only slightly increased. For mindfulness, positive stimuli evoked stronger amplitudes after the intervention, while EPN for negative stimuli increased from T1 to T2. Conclusion Distinct effects were observed for the EPN for pictures with negative valence. Here, it is presumed that mindfulness treatment led to a refocusing of attention with a focus on positive valence, whereas NF seems to entail a different processing of images with negative valence and is therefore to be seen more in the sense of a confrontational approach. Our results suggest that both interventions are suitable for modulating EPN. However, it is not clear to what extent the effects are due to the interventions alone and how other factors might have affected the amplitudes, which highlights the need for further research in this area.